Outcomes of non-infectious Paediatric uveitis in the era of biologic therapy - Megan Cann; Athimalaipet V. Ramanan; Andrew Crawford; Andrew D. Dick; Sarah L. N. Clarke; Fatima Rashed; Catherine M. Guly (BMC, 2018)
Abstract Background There is a paucity of data on the ocular outcomes in paediatric non-infectious uveitis since the introduction of the biologic agents. The purpose of this study was to outline the clinical characteristics of children with non-infectious uveitis and determine the visual outcomes and ocular complication rates in the modern era. Methods Children with non-infectious uveitis from January 2011 to December 2015 were identified. Data was collected at baseline, 1, 3, 5, and 10 years post diagnosis. The incidence rates of visual impairment, structural ocular complications and surgical intervention were calculated. Using logistic regression the association between various baseline characteristics and later visual impairment was investigated. Results Of the 166 children, 60.2% (n = 100) had a systemic disease association. 72.9% (n = 121) children received methotrexate, 58 children progressed to a biologic. The incidence rates of visual acuity loss to > 0.3 LogMAR (6/12) and to ≥1.0 LogMAR (6/60) were 0.05/Eye Year (EY) and 0.01/EY, respectively. Visual outcomes in the Juvenile Idiopathic Arthritis associated Uveitis (JIA-U) and Idiopathic Uveitis cohorts were not statistically significant. Of the 293 affected eyes, posterior synechiae was the predominant complication on presentation, while cataract had the highest incidence rate (0.05/EY). On direct comparison, children with JIA-U were statistically significantly more likely to develop glaucoma while children with Idiopathic Uveitis were statistically significantly more likely to develop macular oedema. Conclusion One third of children received a biological therapy, reflecting increasing utilisation and importance of biological agents in the management of inflammatory conditions. Rates of visual impairment and ocular complications are an improvement on previously published data.